Diferentes dosagens da suplementação aguda de cafeína interferem em parâmetros neuromusculares durante um teste de resistência muscular? - Saborosa, Guilherme Pereira (2023)
Introduction: Caffeine is considered one of the main nutritional ergogenic resources (REN) that from doses between 3 – 6 mg.kg-1 promote different actions, mainly in the central nervous system, inhibiting adenosine receptors, sports physical performance, becoming an important aid promoting the improvement of neuromuscular responses in a resistance exercise, enhancing performance and work capacity. Objective: To verify the effects of different doses (210 mg and 420 mg) of acute caffeine supplementation on muscular endurance performance, glucose concentration, capacity and neuromuscular activation. Methodology: Based on a randomized, double-blind clinical trial, 11 participants (25.7 ± 5.9 years; 71.1 ± 11.0 Kg; 170.72 ± 6.6 cm; 12.49 ± 3.8% F) male, with practical experience in RT. Six face-to-face visits were carried out. The 1st visit was due to: pre-glucose, assessment of anthropometric measurements, muscle thickness of the Pectoralis Major (PM), 24-hour Food Recall (R24H), Maximum Isometric Voluntary Contraction Test (CVIM) identifying the peak of the Electromyography (EMG) of PM in its clavicular and sternal portion, in addition to the one repetition Maximum test (1RM), and post-test glucose. In all visits, pre- and post-test glucose, muscle thickness, 24HR and EMG were analyzed. After 48 hours, the 2nd visit was performed with the muscular endurance test in the bench press with 80% of 1RM. All other visits were satisfied. The 3rd, 4th, 5th and 6th visit had caffeine supplementation and/or placebo in capsules 60 minutes pre-test of muscular endurance. Caffeine had a low dose (LC) of 210 mg and a high dose (CA) of 420 mg, whereas the low placebo (PB) was 230 mg and the high (PA) 460 mg. The 3rd visit known as Baseline (BA) took place 48 hours after the 2nd, while the 4th, 5th and 6th occurred 7 days after the previous one. Descriptive statistics were used. Two-Way ANOVA for comparison between conditions with a significance level of p < 0.05, magnitude of variation and delta of variation were used. The paired t-test was used to compare groups and pre- and post-test times. Results: The number of repetitions showed an increase in all conditions compared to BA, without significant differences (p > 0.05). The AC and PA reached the highest averages of repetitions (CB: 12.09 ± 3.33 reps; PA: 12.27 ± 2.72 reps), where the Fiber type II group showed a greater sensitivity to caffeine. was higher (p < 0.05) in all conditions at the post-test moment. The glycemic response showed a significant reduction (p < 0.05) after the test for conditions BA, PB and PA. Conclusion: It is concluded that caffeine influenced the performance of the muscular endurance test. The results liked that their supplementation had a greater influence on type II fibers, promoting greater activation. Thinking about the practice of RT, caffeine supplementation proved to be an attractive supplement for performance.